Molecular Detection of Toxoplasma gondii and Neospora caninum in Domestic Ducks in Hunan Province, China - Lv, Qiu-Yan; Zheng, He-Liang; Yang, Wen-He; Liu, Guo-Hua (Frontiers in Veterinary Science, 2021)
Toxoplasma gondii and Neospora caninum are protozoan parasites that infect warm-blooded animals, and cause major economic losses in livestock industries worldwide. However, little is known about the genotypes of T. gondii and N. caninum in domestic ducks in China. Herein, brain samples from 588 domestic ducks from Hunan province in China were examined for the presence of T. gondii and N. caninum. Polymerase chain reaction (PCR) was used to detect T. gondii B1 gene and N. caninum NC-5 gene. Forty-five DNA samples (7.7%; 95% CI: 5.5-9.9) were positive for B1 gene, and two (0.3%; 95% CI: 0-0.7) were positive for NC-5 gene. The risk factors significantly associated with T. gondii infection were age and sex. The 45 samples positive for T. gondii were genotyped using multi-locus PCR-RFLP analysis and only one sample was fully genotyped as ToxoDB#9 (Chinese I). These results provide new information about the epidemiology of T. gondii and N. caninum in ducks in Hunan province in China. The data also highlight the importance of a “One Health” approach to dealing with toxoplasmosis.